Breastfeeding beliefs and practices among employed women: A Thai cultural perspective - Yimyam,S. (2015)
Breastfeeding is a natural female function, and is also a customary method of infant feeding. In Thailand, breastfeeding initiation is a nearly universal practice. However, breastfeeding duration was shortened. This chapter derives from a combined qualitative and quantitative study that investigated the relationship between socio-economic, cultural factors, and breastfeeding among 300 employed women in Northern Thailand. The study found that Thai women have positive attitudes toward breastfeeding and breast milk in terms of the nutritious, immunological, behavioral, and economic benefits. The peak rates of breastfeeding at 1 month also coincide with the period of confinement 'yu duan'. Within this period, the women have to rest at home and are relieved of all household duties chores, only caring for their infants for a month. Generally, these traditional beliefs and practices provide an opportunity for the women to adjust to their new role as a mother. Since both mother and baby always stay together, they can learn from each other. Moreover, strong social endorsement of the value of breastfeeding (and the obligation it places on the next generation) reinforces the benefits of breastfeeding during confinement. However, some cultural beliefs and practices can act as barriers to breastfeeding. These include perceptions that 'breastfeeding can cause infant illness', 'there is no breast milk in the first few days', 'breast milk later in lactation is inadequate in nutritional value', and the practice of giving a bottle of water or formula at an early age. Together with a lack of knowledge about the mechanics of breastfeeding, or how to solve breastfeeding problems, these notions may diminish confidence and lead to early weaning. Therefore, it appears that cultural beliefs and practices, combined with support from family members, may be the most important factors influencing breastfeeding practices in the first month in northern Thailand. © 2011 Springer Science+Business Media, LLC.